Genetic linkage of oxidative stress with cardiometabolic traits in an intercross derived from hyperlipidemic mouse strains. (January 2020) - Fuller, Daniela T.; Grainger, Andrew T.; Manichaikul, Ani; Shi, Weibin
Abstract: Background and aims: Oxidative stress is associated with cardiometabolic traits in observational studies, yet the underlying causal relationship remains unclear. Apolipoprotein E-deficient ( Apoe −/− ) mice develop significant hyperlipidemia and hyperglycemia on a Western diet. Here we conducted linkage analysis to investigate genetic connections between cardiometabolic traits and oxidative stress. Methods: 266 female F2 mice were generated from an intercross between C57BL/6 (B6) and BALB/c (BALB) Apoe −/− mice and fed 12 weeks of Western diet. Plasma levels of HDL, LDL cholesterol, triglycerides, glucose and malondialdehyde (MDA) and atherosclerosis in aortic root and left carotid artery were measured. 127 microsatellite markers across the genome were genotyped. Results: One significant locus at 78.3 cM on chromosome (Chr) 1 (LOD score: 3.85), named Mda1, and two suggestive loci near 60.3 cM on Chr1 (LOD score: 2.32, named Mda2 due to replication in a separate cross) and 19.6 cM on Chr4 (LOD score: 2.34) were identified for MDA levels. Mda1 coincided precisely with loci for LDL, triglyceride, glucose, and body weight and overlapped with a locus for atherosclerosis in the aortic root. Plasma LDL, triglyceride, and glucose explained 25.5, 19.2, and 24.2% of the variation in MDA levels of F2 mice, respectively. After correction for triglyceride or LDL, QTLs for MDA on Chr1 and Chr4 disappeared. QTLs on Chr1 disappeared, remained on Chr4, and additional QTLs on Chr12 and Chr13 were detected after correction for glucose. The QTL on Chr12, named Mda3, had a significant LOD score of 8.034 and peaked 62.22 at cM. Conclusions: We demonstrated a causative role for cardiometabolic traits in oxidative stress and identified hyperlipidemia and hyperglycemia as a major driver of oxidative stress. Graphical abstract: Image 1 Highlights: Malondialdehyde (MDA), a oxidative stress marker was found controlled by a significant QTL on chromosome (Chr) 1 and 2 suggestive QTLs on Chr 1 and 4. Mda1 for MDA coincided precisely with loci for LDL, triglyceride, glucose, and body weight. Plasma LDL, triglyceride, and glucose each accounted for 20% of the variance in MDA levels of F2 mice. After correction for triglyceride or LDL, QTLs for MDA on Chr 1 and 4 disappeared.